J is for judgment eaudiobook - Grafton, Sue (Kinsey Millhone, 2007)
2 cassettes / 3 hours Read by Judy Kaye Once again, Kinsey Millhone, America's favorite female P.I., embroils herself in a complex and entertaining Alphabet Murder Mystery.   When Wendell Jaffe, mastermind of a real-estate scam, disappeared at sea, nobody was found.  Now, five years later, he's declared legally dead and California Fidelity has to pay up on his life insurance policy . . . to the tune of half a million dollars.  Soon after, the tune slides off-key when Jaffe is spotted in Mexico - and Fidelity hires Kinsey Millhone to sort things out.  Oddly enough, Kinsey's investigation of the con man's past triggers a surprising inquiry into her own family history,.  And, as the two stories intertwine, our favorite P.I. finds herself facing dangerous consequences.